Traditional Crafts of Rural People of Fergana Valley - Ziyodbek Yuldashevich Esonov (International Journal on Human-Computing Studies, 2021)
This article covers the history of traditional handicrafts of the rural population of the Fergana Valley in the late XIX - early XX centuries. The main focus is on the development of blacksmithing, pottery and textile crafts in the villages of the Fergana Valley, changes in the industry, the factors that led to the emergence of centers. The comments made were analyzed on the basis of factual material